2007
DOI: 10.1057/9780230210752
|View full text |Cite
|
Sign up to set email alerts
|

Presupposition and Implicature in Compositional Semantics

Abstract: Palgrave Studies in Pragmatics, Language and Cognition is a series of high quality research monographs and edited collections of essays focusing on the human pragmatic capacity and its interaction with natural language semantics and other faculties of mind. A central interest is the interface of pragmatics with the linguistic system(s), with the 'theory of mind' capacity and with other mental reasoning and general problem-solving capacities. Work of a social or cultural anthropological kind is included if firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 56 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Fox 2007;Spector 2007) have suggested that a silent exhaustivity operator Exh might strengthen the meaning of natural language or and cause it to be interpreted as an exclusive rather than inclusive disjunction (see also Nute 1975). Thus, the use of Exh can break de Morgan's law.…”
Section: Ruling Out Alternative Accounts For Our Findingsmentioning
confidence: 99%
“…Fox 2007;Spector 2007) have suggested that a silent exhaustivity operator Exh might strengthen the meaning of natural language or and cause it to be interpreted as an exclusive rather than inclusive disjunction (see also Nute 1975). Thus, the use of Exh can break de Morgan's law.…”
Section: Ruling Out Alternative Accounts For Our Findingsmentioning
confidence: 99%
“…Free-choice inferences, which have been treated as cases of scalar implicatures(Fox 2007), also appear to be processed differently from run-of-the-mill scalar implicatures(Chemla and Bott 2014).15 For simplicity, we analyze transitive predicates like lifted the piano and surrounded the castle as 1-place rather than 2-place predicates.…”
mentioning
confidence: 99%